Role of Social Media Motives in Driving Consumer Buying Behaviour in Online Brand Community of Pakistan - Rehman, Waiza; Khattak, M. Arif; Khurshid, M. Asif; Saif, Mian M. Osman Bin (International Journal of Psychosocial Rehabilitation, 2020)
In this era of mushroom growth of companies, it is essential for companies to engage the consumers with them for long run. Social media is the most used tool now in this digital world. This paper intended to explore the role of social media motives in consumer engagement and further on brand loyalty. This study enlighten the impact of social media motives i.e. information, environment, social aspect and self-seeking status on consumer engagement, further the impact of consumer engagement on consumer’s brand loyalty is also observed. The sample of 255 was taken from population of Pakistan. The study focused on online survey strategy through purposive data sampling technique. Path analysis of structural equational modelling via AMOS and moderated regression analysis via SPSS were applied. The study elaborates that there is a strong and positive relationship between consumer engagement and social media motives. Whereas consumer engagement plays adequate role in developing brand loyalty in online brand community. Companies can build marketing strategies that are fixated on these four motives in order to engage and lead to being loyal in this digital era.